Analisis Kritis Gaya Hidup Konsumtif di Era Disrupsi Perspektif Q.S. Al-A’raf: 31 dalam Tafsir Al-Misbah - fithrotin; Baiti Sekar Wangi; Sahro Wardil Lathif (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
Consumptive lifestyle, where individuals buy goods or services excessively without considering their needs and financial capabilities, has become a prevalent phenomenon in the modern era. This is driven by various factors, such as easy access to information and products, aggressive promotions and advertisements, and the rapid development of materialistic culture. Although consumptive lifestyle can provide instant satisfaction, in reality, it can have significant negative impacts on both individuals and society as a whole. The aim of this research is to analyze the Quran's perspective on consumptive lifestyle in the era of disruption and formulate restorative solutions based on the interpretation of Al-Misbah. This research method uses descriptive content analysis, focusing on the understanding of the meanings and interpretations of texts, particularly Al-Misbah's interpretation, related to a consumptive lifestyle. The data collection methods include primary data from Al-Misbah's tafsir as the main source and secondary data from relevant books on the research topic to enrich the analysis and provide a broader context. The research findings show Quraish Shihab's viewpoint on consumptive lifestyle, which is considered a reprehensible trait that can lead individuals to sin and misguidance. They also demonstrate the ideal Muslim's attitude towards shopping and financial management, which involves avoiding extravagance and stinginess, and embracing the principle of balance. The research further strengthens arguments by referring to Quranic verses and Hadiths that prohibit waste and excess.